Efficient Near‐Infrared Emission of Ce3+–Nd3+ CoDoped (Sr0.6Ca0.4)3(Al0.6Si0.4)O4.4F0.6 Phosphors for c‐Si Solar Cell. Issue 1 (24th September 2015) - Chen, Jiajun; Liu, Jie; Yin, Huimin; Jiang, Shuangling; Yao, Hui; Yu, Xibin
Abstract : Ce 3+, Nd 3+ codoped (Sr0.6 Ca0.4 )3 (Al0.6 Si0.4 )O4.4 F0.6 phosphors were synthesized through the high‐temperature solid‐state reaction method. Luminescence spectra, absorption spectra, and decay lifetimes of these samples have been measured to prove the energy‐transfer process from Ce 3+ to Nd 3+ . Under UV and blue light excitation, (Sr0.6 Ca0.4 )3 (Al0.6 Si0.4 )O4.4 F0.6 :Ce 3+, Nd 3+ phosphors exhibit near‐infrared (NIR) emission, mainly peaking at 1093 nm and secondarily at 916 nm. The NIR emission matches well with the band gap of c‐Si. Results of this work suggest that the (Sr0.6 Ca0.4 )3 (Al0.6 Si0.4 )O4.4 F0.6 :Ce 3+, Nd 3+ phosphors have potential application as down‐shifting luminescent convertor for enhancing the photoelectric conversion efficiency of c‐Si solar cell.